Spot, log, map: Assessing a marine virtual citizen science program against Reed's best practice for stakeholder participation in environmental management. (1st January 2018) - Nursey-Bray, Melissa; Palmer, Robert; Pecl, Gretta
Highlights: Redmap generates data about the potential impacts of climate change on the marine environment. Redmap develops a novel capacity for date entry. Redmap is a platform for social learning and trust building. VCS have capacity to act as virtual boundary organisations.